The Relationship between Teamwork and the Performance of Medical Staff of Shahid Rajaei Cardiovascular, Medical and Research Center in Tehran, Iran in 2016 - F Mirzaei; SJ Tabibi (Iran University of Medical Sciences, 2020)
Background & Aims: The present study aimed to evaluate the relationship between teamwork and performance of the medical staff of Shahid Rajaei Cardiovascular, Medical and Research Center in Tehran, Iran. In a health system, teamwork is highly important for increasing the quality of services and the provision of safe and effective care. In addition, teamwork is recognized as an integral part of safe and efficient performance in a hospital. In addition, patient safety and health are considered a critical issue in the health systems of various countries. Therefore, teamwork and communication to prevent and reduce the medical staff's errors are of utmost importance. The present study was carried out to assess the relationship between the teamwork of nurses and the performance of the medical staff of Shahid Rajaei Cardiovascular, Medical and Research Center in Tehran. Materials & Methods: This descriptive-analytical research was performed in 2016. The statistical population included all nurses with a BSc, MSc, or higher degree working at medical centers of the university (n=290). The present research was carried out as correlational research, which is a type of descriptive study (non-experimental) that evaluates the relationship among variables based on research objectives. In total, 290 individuals were selected by simple non-random sampling method, and data were collected using a staff performance questionnaire by Choharie et al. and a teamwork questionnaire by Luncheon. The validity and reliability of the researcher-based questionnaire used in the present study were confirmed, and data analysis was performed in SPSS version 16 using the Pearson correlation coefficient and t-test. Results: In the evaluation of the correlation of two variables, the Pearson correlation coefficient will be applied if both variables are in relative and distance scale. If the correlation coefficient of the population is ρ and the correlation coefficient is a sample with n volume of the population r, r might be obtained randomly. To this end, we exploited the significance test of the correlation coefficient to determine whether the two variables were random or independent. In other words, the question was: are the correlation coefficient of community zero or not. The coefficient estimates the level of correlation between two distance or relative variables with a value in the range of +1 and -1. A positive value is interpreted as changes occurred in the two variables in the same direction. In other words, an increase in one variable leads to an increase in the other variable. On the other hand, a negative r value means that the two variables operate in the opposite direction. In other words, an increase in the value of one variable decreases the value of the other variable and vice versa. In addition, a zero value shows the lack of relationship between the two variables, whereas a positive and negative value is indicative of a completely positive and completely negative correlation, respectively. In the present study, the mean and standard deviation of the components of teamwork and performance of the staff was estimated at 3.28 ± 0.69 and 3.64 ± 0.55, respectively. Moreover, the mean of dimensions of commitment, trust, accountability, constructive approach, and purposefulness was reported to be 3.21 ± 0.75, 3.18 ± 0.84, 3.18 ± 0.80, 3.34 ± 0.75, and 3.54±0.90, respectively. According to the Pearson correlation coefficient, there was a direct and significant relationship between the performance of the staff and teamwork among clinical employees (0.514<r Conclusion: According to the analysis performed, teamwork is a dynamic process, which includes two or several professional members sharing common treatment goals, necessary health skills, and specialties, who work with each other in an intimate working environment for solving specific and common goals. Team processes are a vital component of forming a coherent, committed, and united treatment team. Every year, healthcare providers are expected to use fewer employees with higher treatment safety. The importance of having a robust medical team and teamwork is highlighted due to the shortage of personnel and educational costs, medical errors, and increasing patient expectations. Teamwork in the healthcare field is so crucial that numerous studies have been conducted on training medical staff and team-making topics. It is notable that the organizations that apply teamwork have experienced significant improvement in their staff's creativity, productivity, and satisfaction. According to the results, the level of teamwork among the staff was above average. Nonetheless, their teamwork should be enhanced to reach higher levels. In addition, managers in various sectors and hospital management should pay more attention to people's achievements and use their opinions. Moreover, they should teach teamwork and related skills to their staff and use the necessary control levers in group management. All of these measures will ultimately lead to reduced possibility of re-hospitalization, decreased duration of hospital stay, and improved safety and performance results of the medical staff. Teamwork is not the regular placement of individuals in a specific location. In fact, teamwork requires adapting to each otherchr('39')s performance, understanding the treatment needs, being able to anticipate the priorities of others, and acclimating to changes in the environment. In addition, teamwork is required for better patient management and establishment of treatment safety. The results were indicative of a significant relationship between teamwork and performance of the medical staff of Shahid Rajaei Cardiovascular, Medical and Research Center in Tehran with the components of commitment (coefficient of), trust (coefficient of 0.79), accountability (coefficient of 0.84), constructive approach (coefficient of 0.77), and purposefulness (coefficient of 0.78). furthermore, strengthening teamwork among various employees and establishing educational workshops on communication skills can contribute to the improvement of staff's performance.</r